Need for oral health awareness among students in Nigeria - Nweke, Francis C.; ADAMU, VE; Eneojo, Ndidiamaka Ijeoma (Orapuh Journal, 2020)
Oral health refers to a state of not having chronic orofacial pain, oral and throat cancers, or birth defects, oral infections and ulcers, periodontal disease, tooth loss, and other disorders that affect the oral cavity. Oral health awareness remains an excellent means of promoting the upkeep of people’s oral health by the dental team. Oral health is usually not taken seriously, but it is an essential part of our daily life. Good oral health awareness among people will enhance the power to talk, smile, smell, taste, touch, chew, swallow, and convey feelings among other emotions through facial expression as a result of individuals being attentive to oral health and maintaining it. Several studies focused on selected Nigerian student-populations have indicated a low level of oral health awareness and poor attitudes to oral health matters. This may be because people are not well informed about the steps required to prevent oral diseases or treat them. Concerning dental visiting habits, also, people are quite indifferent. The most frequent reasons for visiting are having a toothache, a perceived need for tooth extraction, and a need for prosthetic treatment. To handle the low level of oral health awareness that pervades the Nigerian student community at the present, it is important to prime the combined efforts of Dental Health Care Professionals (DHCP), the government, and non-governmental organizations in tackling the menace by urgently improving access to oral health information and education, especially, among students.